MEUNASAH DAN KETAHANAN MASYARAKAT GAMPONG - Sabirin, Sabirin (Jurnal Ilmiah Peuradeun, 2014)
Build Aceh's post- conflict and tsunami is a process of reform in the form of a new civilization without leaving his identity, people’s lives by creating a secure, peaceful, prosperous and equitable. As a nation rich in cultural values, with meunasah as a community center of village (village community center) has been able to bring Aceh into a great nation. Meunasah as Acehnese cultural assets expected to always be a source of energy that should be used as well as possible to make Aceh superior, advanced, and is growing at a high civilization and glorious civilization in the arena of the world without leaving the local values (local wisdom/ wisdom). Besides Meunasah there are also two other agencies that have similar functions and similarities in the rebuilding of Aceh, namely mosques and Islamic boarding schools. The trio is a milestone that has become a source of re-inspire and re-spirit to find a future, not just for the localism, but also for non-localism in building the dignity of all his Aceh, the balance between "Recitation and Thought "towards the welfare of a just society as part of a peaceful world civilization (peace civilization).